2022
DOI: 10.1186/s12890-022-01888-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation and sympathetic activation in gestational diabetes mellitus with obstructive sleep apnea

Abstract: Background Although some evidence suggests an association between obstructive sleep apnea (OSA) and gestational diabetes mellitus (GDM), its consequences still remain largely unknown. We sought to determine whether OSA is associated with higher inflammation and sympathetic levels in GDM, and to relate them with insulin resistance and perinatal outcomes. Methods OSA was identified by polysomnography and defined as an apnea–hypopnea index of ≥ 5 h−1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The remaining 49 articles were screened, and 18 articles were excluded for various reasons, such as lack of a control group, lack of data, studies published in languages other than English or Chinese, unclear measurement units, case reports, and reviews. Finally, 25 papers [11,12,23–45] comprising 31 studies were included in the current meta-analysis, as showed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 49 articles were screened, and 18 articles were excluded for various reasons, such as lack of a control group, lack of data, studies published in languages other than English or Chinese, unclear measurement units, case reports, and reviews. Finally, 25 papers [11,12,23–45] comprising 31 studies were included in the current meta-analysis, as showed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published from 2002 to 2022. Among these studies, 11 studies [11,[24][25][26]29,30,32,36,[41][42][43][44][45] reported the relationship between plasma IL-10 levels and OSAHS, A study reported differences in IL-10 levels in tonsil tissue between OSAHS patients and non-OSHAS patient, [22] and 19 studies [12,23,27,28,31,[33][34][35][37][38][39][40] reported the relationship between the serum IL-10 levels and OSA. The determination methods of IL-10 varied across the studies; however, most of them use enzyme-linked immunosorbent assay (ELISA).…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Currently, there is still relatively limited studies on the relationship between different OSA phenotypes and cardiovascular complications. A study by Al Oweidat K et al found that rapid eye movement OSA was more common in patients with type 2 diabetes, and was associated with factors related to insulin resistance such as sympathetic nerve activity and increased IL-1b [ 47 , 48 ]. Accurately identifying the different phenotypes of OSA is crucial for clinicians, which helps them to develop more precise and effective treatment plans for their patients, thus reducing the negative impact on cardiac structure and myocardium [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A decreased baroreflex sensitivity may be provoked by repetitive blood pressure surges during sleep and increased SNS activation [ 74 , 75 ]. Some authors have proven that increased SNS activation leads to elevated interleukin concentrations in OSA patients [ 76 ] ( Figure 2 ).…”
Section: Osa Inflammation and Painmentioning
confidence: 99%